Hubungan Gaya Hidup Dan Keputusan Pembelian Gen Z Terhadap Peningkatan Mutu Telur Asin - Oktaviana Ratna Sari Dewi; Ajat Sudrajat (Universitas Muhammadiyah Metro, 2025)
This investigation aims to understand how the lifestyle of Gen Z individuals can influence their purchasing decisions regarding the improvement of salted eggs quality, influenced by the impact of technology and social media on their daily habits, including food choices. The research method employed was through an online survey by distributing a Google Form randomly to various age groups within Gen Z, with a sample size of approximately 100 respondents. The data obtained were then processed through validity and reliability tests, classical assumption tests (normality test, multicollinearity test, and heteroskedasticity test), multiple linear regression analysis, and hypothesis testing. The results of the analysis calculation indicate that the related variables are valid and reliable, the data are normally distributed, and there is no indication of multicollinearity or heteroskedasticity. For partial testing, it shows that the independent variables in the study, namely lifestyle (X1) with a calculated t-value of 2.761 > the tabulated t-value of 1.984, and purchasing decisions with a calculated t-value of 3.150 > the tabulated t-value of 1.984, meaning they contribute significantly to each independent variable towards the dependent variable, which is the improvement of salted eggs quality. Meanwhile, simultaneous testing obtained an F-value of 6.356 > the tabulated F-value of 3.090, indicating that both lifestyle (X1) and purchasing decision (X2) variables collectively contribute significantly to the improvement of quality (Y). Thus, the main conclusion drawn is that there is a strong connection between Gen Z's lifestyle and their purchasing decisions regarding the improvement of salted eggs quality.